2020 Focus briefs on the world's poor and hungry people - International Food Policy Research Institute (International Food Policy Research Institute, 2007)
Assessing the world’s progress against poverty calls for frequent and careful measurements, using household surveys and price data. Fortunately, the task of measuring poverty is becoming easier, and the results are probably getting more accurate over time. The best data for assessing progress against poverty come from surveys of the living standards of nationally representative samples of households. In the past 25 years there has been enormous progress in designing, implementing, and processing such surveys for developing countries, thanks in large part to the efforts of national statistics agencies throughout the world and the support of the donor community and international development agencies. These data provide key information about global and regional progress in alleviating poverty.